Strategi Afektif Dalam Mengatasi Permasalahan Pemalu Pada AUD: Faktor Penyebab, Pendekatan, Dan Dampak Psikososial - Rizky Aprilia Pratiwi; Syafrudin, Ulwan; Oktaria, Renti (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
The problem of shyness in early childhood cannot be left alone because it will affect their personality. The existence of this study aims to find out about what are the causal factors of shyness problems in children aged 8 years and how to deal with these shy problems. This study uses a qualitative approach to the type of case study. With the main subject of the research is an 8 year old child in the sub-district of Tanjung Senang, the city of Bandar Lampung. The results of this study found that the factors causing the problem of shyness in children consisted of internal factors and external factors. The ways that can be done to overcome the problem of shyness are by inviting their children out of the house to interact with neighbors, introducing children to children their age, encouraging children to play with friends outside the home, and limiting children from using cellphones so that children are not engrossed in themselves.